Two-loop RG functions of the massive φ4 field theory in general dimensions - Shpot, M.A. (Condensed Matter Physics, 2010)
Two-loop Feynman integrals of the massive φ4d field theory are explicitly obtained for generic space dimensions d. Corresponding renormalization-group functions are expressed in a compact form in terms of Gauss hypergeometric functions. A number of interesting and useful relations are given for these integrals as well as for several special mathematical functions and constants.